2017
DOI: 10.1177/1177625017701106
|View full text |Cite
|
Sign up to set email alerts
|

Time Course Expression Analysis of 1[2-cyano-3,12-dioxooleana-1,9(11)-dien-28-oyl]imidazole Induction of Cytoprotection in Human Endothelial Cells

Abstract: 1[2-cyano-3,12-dioxooleana-1,9(11)-dien-28-oyl]imidazole (CDDO-Im), a synthetic derivative of oleanolic acid that exhibits antioxidant and anti-inflammatory activity in several animal and in vitro models, has been shown to be beneficial if given after injury. Although induction of heme oxygenase 1 appears to be a major effector of cytoprotection, the mechanism by which the overall effect is mediated is largely unknown. This study evaluated temporal gene expression profiles to better characterize the early tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Observed SM-induced up-regulation of KLF4 is in accordance with published data: it was shown that CDODA-Me and cyano enone-bearing derivative of betulinic acid induced KLF4 expression in colon cancer cells (1-5 μM (SW480, HT-29, HCT-15 cells (12 h)) and 5-10 μM (SW80, HT-29 cells (24 h)), respectively) [53, 126]. Along with KLF4 , other CESC-associated DEGs DUSP1 , EGR1 and FOS were found to be sensitive to treatment with cyano enone-bearing triterpenoids: up-regulation of these genes and their proteins were detected in HUVEC and VC1 cells treated by CDDO-Im (0.05-0.2 μM (0.5–6 h)) [66, 127, 128].…”
Section: Discussionmentioning
confidence: 99%
“…Observed SM-induced up-regulation of KLF4 is in accordance with published data: it was shown that CDODA-Me and cyano enone-bearing derivative of betulinic acid induced KLF4 expression in colon cancer cells (1-5 μM (SW480, HT-29, HCT-15 cells (12 h)) and 5-10 μM (SW80, HT-29 cells (24 h)), respectively) [53, 126]. Along with KLF4 , other CESC-associated DEGs DUSP1 , EGR1 and FOS were found to be sensitive to treatment with cyano enone-bearing triterpenoids: up-regulation of these genes and their proteins were detected in HUVEC and VC1 cells treated by CDDO-Im (0.05-0.2 μM (0.5–6 h)) [66, 127, 128].…”
Section: Discussionmentioning
confidence: 99%
“…The possible mechanisms for CDDO-Im cytoprotection were attributed to the induction of HO-1, activation of Nrf2 signaling pathway in response to oxidative stress, and elevation of the expression of heat shock proteins [ 8 ]. A recent time-course study revealed gene expression pattern induced by CDDO-Im in human endothelial cells [ 13 ]. Genes that upregulated by this compound within an hour include early growth response gene 1, 2, and 3.…”
Section: Cytoprotection Of Natural Compoundsmentioning
confidence: 99%
“…This activation of RAF1 leads to phosphorylation of the tyrosine and threonine residues of MAP2K1which then leads to activation and transduction of the MAPK/ERK pathway. Another crucial element of CDDO-Im analysis by Bynum et al [ 13 ] is the identification of the DUSP1 gene at the 0.5 hour point. There are several anti-inflammatory drugs that also act through the DUSP1 gene including glucocorticoids [ 65 ].…”
Section: Cytoprotection Of Natural Compoundsmentioning
confidence: 99%